Fabrication of modal analysis test rig for clamped-clamped boundry condition - Mohd Hafiz, Razilah (2010)
The main focus of this project is to design and fabricate a mini modal analysis test rig for clamped-clamped boundary condition. The design generation of this project and solid three dimensional structures modelling of the test rig was developed using solidworks software. This test rig was made using iron angle and hollow square bar and went through a few fabricating process such as measuring, cutting, welding and finishing. It was successfully been done and able to support a modal analysis specimen for maximum length of plate is 20cm to 30cm.